Meta-análise em rede na comparação de anticoagulantes para tratamento de tromboembolia venosa associada ao câncer - Silva, Fernanda Borim da (Universidade Federal de São Carlos, 2025)
Cancer-associated venous thromboembolism (CAVTE) is a common complication in oncology patients and is associated with a high risk of morbidity and mortality. Several anticoagulants are used for its treatment; however, the lack of direct comparisons among all available therapeutic options makes the optimal clinical choice challenging. In this context, this study conducted a network meta-analysis using a Bayesian hierarchical approach to compare the efficacy and safety of the anticoagulants Dalteparin, Apixaban, Rivaroxaban, and Edoxaban, integrating both direct and indirect evidence from six randomized clinical trials. The modeling was carried out using a random-effects binomial framework and Monte Carlo Markov Chain (MCMC) algorithms implemented in the R software. The results indicate that Apixaban performs best in terms of efficacy, while Dalteparin shows a superior safety profile, especially concerning non-major clinically relevant bleeding events. The findings reinforce the value of network meta-analysis as a decision-support tool in clinical contexts involving multiple therapeutic alternatives.
Network meta-analysis comparing anticoagulants for the treatment of cancer-associated venous thromboembolism
Keywords: Abordagem hierárquica Bayesiana; DOAs; Efeitos aleatórios; Métodos MCMC; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::INFERENCIA PARAMETRICA